2017
DOI: 10.1021/acs.macromol.7b01048
|View full text |Cite
|
Sign up to set email alerts
|

Depolarized Scattering from Block Copolymer Grains Using Circularly Polarized Light

Abstract: The grain structure of ordered block copolymer materials affects their viscoelastic, adhesive, optical, and electrical properties. Depolarized light scattering has proven to be an important method for characterizing this grain structure. In this paper, we use both theory and experiments to demonstrate the relationship between grain structure and depolarized light scattering from ordered block copolymer samples performed with crossed circular polarizers. We model the sample assuming it comprises randomly orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…The sample was placed between crossed polarizers in a heating block that was electrically heated by two heating elements, and the temperature of the sample was controlled by an Omega Engineering temperature controller (CN9111A). 40 In order to determine the order-disorder transition temperature (T odt ) of the sample, the birefringence method was employed. 41 In the orderto-disorder experiments, the total depolarized transmitted laser power was obtained as the sample was heated in approximately 10 °C increments from 80 °C to 110 °C.…”
Section: Depolarized Light Scattering (Dpls)mentioning
confidence: 99%
“…The sample was placed between crossed polarizers in a heating block that was electrically heated by two heating elements, and the temperature of the sample was controlled by an Omega Engineering temperature controller (CN9111A). 40 In order to determine the order-disorder transition temperature (T odt ) of the sample, the birefringence method was employed. 41 In the orderto-disorder experiments, the total depolarized transmitted laser power was obtained as the sample was heated in approximately 10 °C increments from 80 °C to 110 °C.…”
Section: Depolarized Light Scattering (Dpls)mentioning
confidence: 99%
“…The samples used in the DPLS experiments were prepared by melting The schematic of a custom-made apparatus used in the DPLS measurement was described in ref 34 . The light source in this study was a Coherent continuous-wave diode laser with wavelength of 633nm and an output power adjustable from 0 to 40 mW.…”
Section: Depolarized Light Scattering (Dpls)mentioning
confidence: 99%
“…At each temperature step for the shallow quench and deep quench, linear and circular scattering patterns (LP and CP) were captured, one without and the other with the two quarter-wave plates in the beam path as described in ref 34 . The analysis of both sets of scattering patterns led to similar conclusions.…”
Section: Depolarized Light Scattering (Dpls)mentioning
confidence: 99%
See 1 more Smart Citation
“…This grain structure can affect the mechanical, electrical, and optical properties of the material. When the ordered morphology is lamellar or cylindrical, the grains are optically uniaxial and exhibit form birefringence, and the grain structure can be characterized using depolarized light scattering (DPLS). DPLS complements other BCP characterization methods such as small-angle X-ray scattering (SAXS), small-angle neutron scattering (SANS), and electron microscopy (EM). Although recent studies have shown the potential usefulness of these techniques to determine micron-scale structural features of block copolymers, they are primarily used to determine the ordered morphology on the length scale of the unit cell rather than grain structure. In contrast, all of the DPLS signals from ordered block copolymers arise from the grain structure, as typical unit cell sizes in block copolymers are much smaller than the wavelength of light.…”
Section: Introductionmentioning
confidence: 99%